Higher blood cotinine level is associated with worse cognitive functioning in non-smoking older adults - Fu, Zhenmei; Qi, Guiye; Qu, Zhe; Lin, Xuechun; Xu, Li; Shen, Biyu; Dong, Fanghong; Ge, Song (Frontiers in Neuroscience, 2022)
Introduction Secondhand smoke (SHS) is common in older adults; however, its cognitive effect is unclear. We aimed to examine the association between serum cotinine level and cognitive functioning among non-smoking older adults. Materials and methods A total of 2,703 older adults aged 60 and above from the National Health and Nutrition Examination (NHANES) Survey 2011–2014 were included. Serum cotinine level was analyzed in the laboratory. A level ≤10 ng/ml and a response of “no” to the question “Do you currently smoke?” were used to select non-smokers. Cognitive functioning was measured using the Consortium to Establish a Registry for Alzheimer’s disease Word Learning subtest (CERAD-WL) immediate and delayed recall tests, the Animal Fluency test (AFT), and the Digit Symbol Substitution test (DSST). Multivariable linear regression models were constructed to examine the association between serum cotinine level quartile and test-specific and global cognition z scores adjusting for age, race/ethnicity, education, depressive symptoms, body mass index, alcohol use, smoking history, prevalent coronary heart disease (CHD), stroke, and systolic blood pressure. Results About half of the participants (mean age 70.5 years) were female (53.6%), non-Hispanic White (48.3%), and completed some college and above (50.2%). Multivariate linear regressions with a reference group being those in the 1st quantile (lowest) showed that participants in the 4th quartile (highest) of serum cotinine level had lower immediate recall [β = −0.16, 95% confidence interval (CI) = −0.29, −0.03], AFT (β = −0.19, 95% CI = −0.33, −0.05), DSST (β = −0.27, 95% CI = −0.39, −0.15), and global cognition (β = −0.26, 95% CI = −0.39, −0.14) z scores. Participants in the 3rd quartile had lower immediate recall (β = −0.16, 95% CI = −0.30, −0.02) and global cognition (β = −0.16, 95% CI = −0.29, −0.02) z scores. Participants in the 2nd quartile had lower delayed recall z scores (β = −0.16, 95% CI = −0.29, −0.02). Conclusion Higher serum cotinine level was associated with worse cognitive functioning in non-smoking older adults. Prevention and reduction of SHS in older adults may help protect their cognitive functioning.